In-situ monitoring and modelling of distortion in multi-layer laser cladding of Stellite 6: Parametric and numerical approach. (December 2022) - Thawari, Nikhil; Gullipalli, Chaitanya; Vanmore, Hemant; Gupta, T.V.K.
Abstract: Laser cladding is a direct metal deposition technique used for repair and rebuilding of worn-out components. In this process, the component is subjected to high heating and cooling cycles, which generate residual stresses and distortion affecting the part quality. The present work is to investigate and evaluate distortions generated during deposition using in-situ measuring method and also with numerical modelling. The role of different support conditions (simply, cantilever, and fixed) and process parameters (laser power, scan speed) on distortion are examined. A numerical model in COMSOL Multiphysics software was developed to generate thermal history and distortion in multi-layer cladding of Stellite 6. The temperature data shows large thermal gradients development along the thickness; allowing material to expand and contract at different rates, leading to substrate distortion. This was evidence in laser displacement sensor data and simulation. The results showed simple and fixed supports develop 40–50% and 60–70% less distortion than cantilever. Additionally, when the scan speed is decreased from 20 mm/s to 12 mm/s, distortion is lowered by 15–40%. An increase in laser power from 2400 W to 3400 W showed distortions to be 30–60% higher; while the second layer depositions have given 15–25% lower deflection. The simulation results are in good agreement with experimental values and reveals that support conditions are significant on distortion. Graphical Abstract: Conclusion:- Laser cladding with simple and fixed supports developed 40–50% and 60–70% lower distortions than cantilever support; and increases with increase in laser power and decrease in scan speed. ga1